“Análisis del Convenio de Estrasburgo para verificar su aplicación en el traslado de personas sentenciadas a los centros carcelarios del país de origen”. - Zhindón Macas, Mayeli Karolina (2024)
The present Curricular Integration Work entitled: “Analysis of the Strasbourg Convention to verify its application in the transfer of sentenced persons to prison centers in the country of origin”, arises from the interest of thoroughly analyzing the conditions and procedures established in the Strasbourg Convention, this being the most recognized international instrument in the transfer of sentenced persons and the most used in Ecuador to carry out repatriation processes, in addition to having served as a basis for the celebration of bilateral agreements with other States, which has as its main objective the adequate rehabilitation and reintegration of persons deprived of liberty by allowing them to move to their country of origin so that they continue serving their sentence close to their family, however, in recent years in the face of the prison crisis that the country is going through, the repatriation of sentenced persons has been implemented as a measure to reduce overcrowding and violence in the country's social rehabilitation centers. Therefore, my objective is to make known the conditions and the appropriate procedure for the transfer of sentenced persons, taking into account that the support of the repatriation processes are the international treaties, which facilitate cooperation between States; stating the inconveniences that may occur at the time of applying it, as well as the measures that can be taken to make the transfer of sentenced persons more effective. In this Curricular Integration Work, materials and methods were applied that allowed the correct development of the research, surveys, and interviews were carried out with legal professionals; the results achieved allowed me to show that the repatriation processes of sentenced persons must be made effective and expedited, which would allow the reduction of overcrowding in prisons, as well as guarantee the effective rehabilitation of persons deprived of liberty.